Dukungan Orang Tua Terhadap Motivasi Belajar Siswa Kelas Unggul - Desy Rosmalinda; Marni Zulyanty (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
Abstract. Excellent class students represent students who are considered to have higher intelligence than their peers. The students have to join the exam before, so the school can map the level of their cognitive abilities. Apart from the seriousness of learning, the intelligence possessed by excellent students is inseparable from the existence of parental support. This research supports to see how the form of parental support for students. Data collection is done by collecting questionnaires for students and also parents of students at Al-Falah Islamic Elementary School in Jambi city. Questionnaires have been processed are completed qualitatively so that the data obtained is descriptive. The results of questionnaire analysis are there are various kinds of assistance provided by parents to students, some of them provide a comfortable learning place, consider the needs of children and support every effort undertaken by children. Keywords: excellent class, learning motivation, parental support